The Employment and Income of Female Informal Workers at The Construction Site of Himlam Projects, Tan Phong Ward, District 7, Ho Chi Minh City - Thang, Doan Van (American International Journal of Social Science Research, 2020)
The issue of the employment and income of workers is always a topic that attracts the concerns of sociologists. This study aims to explore the life of female informal workers. The study was conducted at the construction site of Himlam projects, Tan Phong Ward, District 7, Ho Chi Minh City with the participant of 175 female workers and 77 male workers. The questionnaire and interview were employed to collect both quantitative and qualitative data. The findings of the study revealed that the current life of female migrant workers at the construction site of the Himlam project, Tan Hung Ward, District 7, Ho Chi Minh city was facing many difficulties. Their income was low. Also, they were not allowed to sign long-term or definite-term contracts. Therefore, many issues need to be addressed to improve the quality of life and employment of female migrant workers in industrial parks, especially at the Himlam construction site. The government should pay more attention to gender equality and enact policies to improve the living standards of female informal workers. The author expects that the study will partly contribute to the policy-making process in Vietnam.